The most metal-rich asymptotic giant branch stars. Issue 3 (9th November 2021) - Karakas, Amanda I; Cinquegrana, Giulia; Joyce, Meridith
ABSTRACT: We present new stellar evolutionary sequences of very metal-rich stars evolved with the Monash Stellar Structure code and with mesa . The Monash models include masses of 1–8 M⊙ with metallicities Z = 0.04 to Z = 0.1 and are evolved from the main sequence to the thermally pulsing asymptotic giant branch (TP-AGB). These are the first Z = 0.1 AGB models in the literature. The mesa models include intermediate-mass models with Z = 0.06 to Z = 0.09 evolved to the onset of the TP phase. Third dredge-up only occurs in intermediate-mass models Z ≤ 0.08. Hot bottom burning shows a weaker dependence on metallicity, with the minimum mass increasing from 4.5 M⊙ for Z = 0.014 to ≈5.5 M⊙ for Z = 0.04, 6 M⊙ for 0.05 ≤ Z ≤ 0.07 and above 6.5 M⊙ for Z ≥ 0.08. The behaviour of the Z = 0.1 models is unusual; most do not experience He-shell instabilities owing to rapid mass-loss on the early part of the AGB. Turning off mass-loss produces He-shell instabilities, however thermal pulses are weak and result in no TDU. The minimum mass for carbon ignition is reduced from 8 M⊙ for Z = 0.04 to 7 M⊙ for Z = 0.1, which implies a reduction in the minimum mass for core-collapse supernovae. mesa models of similarly high metallicity ( Z = 0.06–0.09) show the same lowering of the minimum mass for carbon ignition: carbon burning is detected in a 6 M⊙ model at the highest metallicity ( Z = 0.09) and in all 7 M⊙ models with Z ≥ 0.06. This demonstrates robustness of the lowered carbon burning threshold across codes.